13 The long-term effects of adipose depot change following bariatric surgery on cardiac geometry. (6th June 2022) - Henry, John Aaron; Abdesselam, Ines; Sorimachi, Hidemi; Rayner, Jenny; Deal, Oscar; Byrne, James; Neubauer, Stefan; Borlaug, Barry; Rider, Oliver
Abstract : Introduction: Total body adipose volume is associated with left ventricular (LV) dilatation (due to increased intravascular volume and cardiac output) while visceral adipose tissue (VAT) is associated with smaller LV cavity size and concentric remodelling (because of insulin resistance). We therefore hypothesised that changes in VAT and total body weight during weight loss would have a differential impact on cardiac geometry. Furthermore, changes in epicardial adipose tissue (EAT), may have an additional mechanical effect by reducing pericardial restraint. We therefore sought to investigate long term changes in VAT, total weight and EAT following bariatric surgery and relate them to cardiac geometry. Methods: Thirty-eight patients underwent cardiac magnetic resonance (CMR) imaging before and after bariatric surgery, including 20 who underwent short-term (median 209 days), 28 medium-term (median 428 days) and 11 long-term (median 1030 days) imaging follow up. Cardiac volumes (left atrial (LA), LV end-diastolic volume (LVEDV) and stroke volume (LVSV)) were assessed using cardiac MRI. VAT was assessed at L5 using a T1 weighted, water suppressed sequence. EAT volumes were calculated by manual contouring in end-ventricular systole on short axis slices from the mitral valve to the apex. Results: Following bariatric surgery all weight loss occurred within 428 days (mean -32kg, 54% excess weight loss, p<0.0001), with no significant change in weight thereafter. VAT loss occurred mostly in the first 209 days (-47%, 84cm2, p<0.0001) with no subsequent change observed at the final two timepoints (Figure 1A). EAT loss occurred in the first 209 days (-13%, mean 10 ml, p<0.0001) with non-significant changes at the two subsequent timepoints (Figure 1B).At 209 days both LA volume (by 13%, p<0.001, Figure 2A) and LVEDV (by 4%, p=0.02, Figure 2B) were reduced. By 428 days whilst LVEDV had not significantly changed (Figure 2B), LA volume increased relative to day 209 (by 11%, p<0.0001). Between 428 and 1030 days LA volume remained the same size, and was similar to preoperative size (p = 0.86). In contrast between 428 and 1030 days LVEDV enlarged (by 11%, p = 0.03), and was similar to preoperative size (p = 0.92). LVSV followed a similar pattern being reduced at 209 days (by 10%, p = 0.002), then increasing after 428 days to become similar to pre-weight loss at 1030 days (p = 0.68). Conclusions: Cardiac volumes show a biphasic response to weight loss, initially becoming smaller and then returning to baseline by 1030 days. We hypothesise that the early drop in LA and LV cavity size is a response to reduced volume from body mass reduction. In contrast, we propose that the increase in LA and LVEDV that follows results from the longer term effects of reducing VAT, and increased space within the pericardium resulting from EAT loss allowing expansion to occur. Conflict of Interest: None